Effect of General Versus Specialized Exercises on Movement Control of Lumbo- Pelvic Region in Subjects with Chronic Low Back Pain - Toma Garbenytė; Vytautas Poškaitis; Vidmantas Zaveckas; Laimonas Šiupšinskas; Rimtautas Gudas (Lithuanian Sports University, 2018)
Research background and hypothesis. Low back pain is a huge problem in the world. One of the main reasons why the low back pain problems arise is lumbo-pelvic motor control dysfunction. Specialized exercises are the basis of physical therapy for low back pain patients. Hypothesis: specialized exercises can be more effective for movement control of lumbo-pelvic region in subjects with chronic low back pain. Research aim was to assess the effect of general versus specialized exercises for movement control of lumbo- pelvic region in subjects with chronic low back pain. Research methods. The study involved 60 subjects with chronic low back pain, 29 women and 31 men, aged 21.5 years on average. All subjects were submitted to the Low Back Pain Duration and Beacke Habitual Physical Activity Assessment  questionnaires  (Baecke  et  al.,  1982).  Lumbo-pelvic  motion  control  was  evaluated  by  six Hannu Luomajoki movement control tests (Luomajoki et al., 2008). Specialized and general training programs were prescribed and performed under supervision of physical therapist. Video materials expert analysis was used for the evaluation of the study data. Research  results.  The  results  showed  that  a  specialized  training  program  was  more  effective  than  general exercises in improving movement control in lumbo-pelvic region for patients with low back pain. Discussion and conclusions. General exercise training program for general exercise group had no effect for all test results. Specialized exercise training program results showed that lumbo-pelvic movement control improved in five of the six control tests (p  < 0.05). Keywords: motor control, physical therapy program, stability, mobility.